Mechanical properties of polycaprolactone microfilaments for muscular tissue engineering - Laura Rojas-Rojas; Teodolíto Guillén-Girón (Tecnología en Marcha)
Polymeric scaffolds can be fabricated as microfilaments to replicate the mechanical characteristics and biological configuration of skeletal muscles and tendons. The microfilaments used in this research were fabricated from polycaprolactone (PCL) pellets by extrusion and a spooling system without using solvents. Their mechanical properties were investigated by applying monotonic and dynamic loads on aligned grouped microfilaments using a customized grip adapter. The fabrication method was simple and produced a homogeneous microfilament with a 90 ± 3 µm diameter. The monotonic tests showed the elasticity of the microfilaments was E = 1863 ± 590 MPa, and their yield strength was σy = 242 ± 45 MPa. The dynamic load test results showed that PCL microfilaments resisted periodic loads for 5.3×105 cycles, retaining a maximum deformation of 55%. The fabricated microfilament has the potential to be used as a biomimetic polymeric scaffold suitable for mechanical stimulation because of its outstanding mechanical behavior during dynamic loading conditions.